DIAGNOSA STATISTIK PEMETAAN PEMAHAMAN BAHASA PEMOGRAMAN SEBAGAI ACUAN UNTUK MEMPERSIAPKAN PENELITIAN MAHASISWA - Heri Herwanto (NUANSA INFORMATIKA, 2019)
Mapping the understanding of student programming languages is very important in facilitating the preparation of the thesis. This study aims to map the understanding of programming languages associated with specialization in research, thesis guidance and institutional policy. The methodology used is a mix method where the analysis is presented qualitatively and quantitatively. The analysis technique used is questionnaire analysis using a Likert scale with software assistance. The results of the analysis found that the majority of respondents are on a scale of 3 to 4, which means that there are agreed and strongly agreed intervals and can be categorized as positive. With this mapping of understanding of the programming language, supervisors and policy makers can get an idea of the potential of students to be developed in producing thesis products and print competitive quality graduates. Keywords: Understanding of Programming Language, Specialization and Thesis Guidance